Clinical management of a complicated crown-root fracture: a case report - Fidel,Sandra Rivera (2011)
This report describes the clinical procedures involved in the treatment of a complicated crown-root fracture in the maxillary left central incisor with a wide open apex of a 10-year-old male patient, due to fall from his own height. Post-trauma treatment comprised cervical pulpotomy and adhesive tooth fragment reattachment. After 1 year, clinical and radiograph examinations showed pulp necrosis and an associated periapical lesion. Endodontic therapy with calcium hydroxide-base intracanal dressing, root canal filling and orthodontic extrusion were performed. Extrusion was completed within approximately 16 weeks and the tooth was restored with a post-core system and a prosthetic crown. After a 3 years of follow-up, there was no evidence of apical periodontitis and the tooth was satisfactory both esthetically and functionally.